1998
DOI: 10.1103/physrevb.58.6258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin-1 impurities in dimerized Heisenberg chains

Abstract: The effects of spin-1 impurities introduced in dimerized antiferromagnetic spin chains are studied using Lanczos diagonalization and quantum Monte Carlo simulations. Firstly, the magnitude of the interaction between a Ni-ion replacing a Cu-ion is derived for the case study system Cu-O-Cu. Then, it is shown that the introduction of S = 1 impurities leads to the suppression of the original spin gap of the dimerized system and to the enhancement of the antiferromagnetic correlations close to the impurity. These f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…These substitutions generate either 3D antiferromagnetism at low temperature (in the case of CuGeO 3 and PbNi 2 V 2 O 8 ) or strong 3D antiferromagnetic correlations (in the case of Y 2 BaNiO 5 ). In these two types of low dimensional spin models, the non magnetic defects generate spin-1/2 moments out of the non magnetic ground state, either in the form of solitons in spin-Peierls systems [31][32][33][34][35][36][37][38], or in the form of "edge" spin-1/2 moments in Haldane gap systems [39][40][41][42]. The available theoretical description of these systems is based on the Dasgupta-Ma real space RG [11,43] describing non magnetic defects in 1D and quasi-1D geometries [30,44,45], and appears to be in good agreement with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…These substitutions generate either 3D antiferromagnetism at low temperature (in the case of CuGeO 3 and PbNi 2 V 2 O 8 ) or strong 3D antiferromagnetic correlations (in the case of Y 2 BaNiO 5 ). In these two types of low dimensional spin models, the non magnetic defects generate spin-1/2 moments out of the non magnetic ground state, either in the form of solitons in spin-Peierls systems [31][32][33][34][35][36][37][38], or in the form of "edge" spin-1/2 moments in Haldane gap systems [39][40][41][42]. The available theoretical description of these systems is based on the Dasgupta-Ma real space RG [11,43] describing non magnetic defects in 1D and quasi-1D geometries [30,44,45], and appears to be in good agreement with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been many theoretical works on the rapid breaking of spin-singlet dimers upon the addition of vacancies in a variety of spingapped models, a procedure which is considered relevant to creating free spins. Some theories showed that staggered spin-spin correlations are enhanced in the vicinity of spin vacancies, [25][26][27][28][29] which accounts for the emergence of the ordered phase in the cationic-substituted 1D magnetic materials CuGeO 3 and SrCu 2 O 3 . 9,10) In the 2D orthogonal dimer SrCu 2 (BO 3 ) 2 , staggered magnetization develops around the triplet excitation in the 1/8 plateau phase.…”
Section: Resultsmentioning
confidence: 99%
“…In the limit x → −∞ one recovers the case of a spin-1 impurity (corresponding to a Ni → Cu substitution) previously studied. 23 Precisely in Ref. 23 it was emphasized the role of the three-site subsystem composed by the S = 1 site and its two S = 1/2 NN sites.…”
Section: Chains With a Single Modified Bondmentioning
confidence: 99%
“…23 Precisely in Ref. 23 it was emphasized the role of the three-site subsystem composed by the S = 1 site and its two S = 1/2 NN sites.…”
Section: Chains With a Single Modified Bondmentioning
confidence: 99%